2023
DOI: 10.1186/s12884-023-05644-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of routine first-trimester ultrasound screening for central nervous system abnormalities: a longitudinal single-center study using an unselected cohort with 3-year experience

Abstract: Background To evaluate the role of a standardized first-trimester scan in screening different kinds of central nervous system malformations and to report a 3-year experience from a tertiary center using an unselected cohort. Methods This was a retrospective analysis of prospectively collected data from a single center evaluating first-trimester scans with predesigned standardized protocols performed between 1 May 2017 and 1 May 2020, involving 39,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hu and colleagues in their cohort study found that detection rate of CNS anomalies in first, second, third and late third trimester were 32%, 22%, 25% and 16%, respectively. These statistics suggest a crucial role of routine USG scans for detection of foetal anomalies 9 . The IUSOG guidelines recommends a transabdominal examination to be performed in two planes in routine practice; the transventricular plane and the transcrebellar plane.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hu and colleagues in their cohort study found that detection rate of CNS anomalies in first, second, third and late third trimester were 32%, 22%, 25% and 16%, respectively. These statistics suggest a crucial role of routine USG scans for detection of foetal anomalies 9 . The IUSOG guidelines recommends a transabdominal examination to be performed in two planes in routine practice; the transventricular plane and the transcrebellar plane.…”
Section: Discussionmentioning
confidence: 94%
“…Leiroz et al 13 in a similar study report sensitivity and specificity of the scan to be 61.1% and 96.3%, respectively. These data suggest a good specificity but fair sensitivity.Hu et al 9 also suggest that 5% of CNS anomalies are missed even after routine ultrasound scans. Improvement on aforesaid parameters may help improve the sensitivity as well as specificity of ultrasound scan.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, US is still the most commonly used method to initially examine the development of the fetal brain for any fetal anomalies during pregnancy. During the 18-to 21-week pregnancy period, US imaging is used to measure the cerebrum, midbrain, cerebellum, brainstem, and other regions of the brain as part of the screening for fetal abnormalities [113,114]. To detect fetal brain abnormalities, Sreelakshmy et al developed a model (ReU-Net) based on U-Net and ResNet for the segmentation of fetuses' cerebellum using 740 fetal brain US images [115].…”
Section: Head and Neck Anomaliesmentioning
confidence: 99%